Students' Self-Reflection on Project-Based Learning in Caption Text Writing - Widarni, Wida (International Journal of English Language and Pedagogy, 2023)
Project-based learning (PjBL) has been shown to increase a variety of abilities in students. This study presents students’ self-reflection on jPBL practices in writing caption text. To acquire data, a qualitative method was used through a questionnaire, interview, and classroom observation. Thirty-five students in the twelfth grade of science at SMA PGRI Cipanas participated in the study. Based on the questionnaire, the average of students’ self-reflection was 51.8% in pre-implementation, 47.7% during the implementation period and 42.3% in post-implementation of PjBL in learning caption text. The results of the interview showed that the students responded positively to caption text writing using project-based learning. The implementation of PjBL in caption text writing can improve students’ writing skills yet most students still made minor mistakes based on the scoring rubrics of simple present tense. They showed positive progress with an average score of 5 or excellent. It is recommended to consider the students' self-reflection in the teaching-learning process in order to determine their competence based on themselves, particularly in their writing skills, and there is a possibility for other researchers to conduct many studies about the students' self-reflection in other skills such as speaking, reading, listening, and other forms such as messages, videos, contents, and so on that can be found in social media.